2003
DOI: 10.1248/bpb.26.1174
|View full text |Cite
|
Sign up to set email alerts
|

Multinucleation of the sodC-Deficient Dictyostelium discoideum

Abstract: The cellular slime mold Dictyostelium discoideum expresses three genes (sodA, sodB and sodC) encoding the extracellular Cu/Zn superoxide dismutases. Following H 2 O 2 treatment, the expression of sodA and sodB increased while that of sodC decreased. The sodC null strain formed multinucleate cells in a shaking culture. These results suggest that sodC plays a unique role in Dictyostelium discoideum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…However, long-term growth on Klebsiella can cause upregulation of NoxB in growing cells ( 136 ). Interestingly, D. discoideum expresses multiple SOD and catalase homologs ( 177 179 ) and exhibits a high resistance to oxidative stress ( 180 ), which suggests that it encounters internally and/or externally generated ROS regularly.…”
Section: Microbicidal Phagosomementioning
confidence: 99%
“…However, long-term growth on Klebsiella can cause upregulation of NoxB in growing cells ( 136 ). Interestingly, D. discoideum expresses multiple SOD and catalase homologs ( 177 179 ) and exhibits a high resistance to oxidative stress ( 180 ), which suggests that it encounters internally and/or externally generated ROS regularly.…”
Section: Microbicidal Phagosomementioning
confidence: 99%
“…SodC message is expressed both in vegetative and aggregative stages, and gradually declined as cells terminally differentiate (Van Driessche et al, 2002;Iranfar et al, 2003). Sequence analysis of SodC revealed a signal peptide as previously suggested (Tsuji et al, 2003), and a previously undescribed C-terminal glycosylphosphatidylinositol (GPI)-anchoring motif ( Fig. 2A).…”
Section: Identification and Characterization Of Sodcmentioning
confidence: 73%
“…Remi56, as well as three other mutants had insertions at the same locus encoding an extracellular superoxide dismutase (SOD) previously identified as SodC (Tsuji et al, 2003). SodC message is expressed both in vegetative and aggregative stages, and gradually declined as cells terminally differentiate (Van Driessche et al, 2002;Iranfar et al, 2003).…”
Section: Identification and Characterization Of Sodcmentioning
confidence: 99%
“…The sequences for the sodA, sodB, (Tsuji et al, 2002) and sodC (Tsuji et al, 2003) genes suggest that they are Cu/Zn enzymes. The sodA and sodB proteins both contain charged amino acids and hydrophobic stretches in the N-termini suggesting that they are extracellular.…”
Section: Antioxidant Defense Mechanisms In D Discoideummentioning
confidence: 99%
“…Studies on D. discoideum sodC showed that expression decreased in the presence of H2O2 and that sodC null cells were multinucleate although the meaning of this was not investigated (Tsuji et al, 2003) and that sodC regulates the small GTPase RAS. D. discoideum sodC null cells have constitutively high activation of Ras, and sodC null cells treated with the scavenger XTT reduced the up-regulation of Ras (Veeranki et al, 2008).…”
Section: Antioxidant Defense Mechanisms In D Discoideummentioning
confidence: 99%